IMPROVING TEACHING ASSIGNMENTS THAT TEACH STUDENTS TO READ AND UNDERSTAND IN PRIMARY EDUCATION - Mirzayeva Dilrabo (Web of Journals Publishing, 2024)
This article discusses the importance of teaching students to read and understand reading in primary education, the content, characteristics, the role and methods of further improving their learning assignments in education and in the student's hierarchy.
Keywords: reading, understanding, understanding, analytical (analytical) reading, reading for study, facial reading, searching, getting acquainted, speech processes.